La infiltración del agua en algunos suelos de los Llanos Orientales y sus implicaciones en su uso y manejo - Amézquita Collazos, Edgar; Londoño, H. (International Center for Tropical Agriculture, 1996)
For a long time it has been accepted that tropical soils, specially oxisols, have excellent physical characteristics, that they are permeables, with high infiltration and drainage rates. However, we have to accept today that tropical soils are very susceptible to degradation by human intervention, especially by the use of intensive and tillage and by rainfall erosivity. Knowing by experience, that soils of the Eastern plains of Colombia are very susceptible to physical degradation, a study to identify the properties that are more vulnerable to use of machinery has been started to try to establish some indicators of degradation. One of the parameters that reflect the actual condition of soils and that is sensible to changes is infiltration, which is really low in the soils that have been studied even under native savanna. This means that they have a low rainfall acceptance capacity and that could behave as "dry soils" under wet clime. The values of infiltration rate found varied from 3 to 15 mm/h for different conditions of use and management systems when it was determined even at different depths.